Laparoendoscopic approach for refractory Roux‐en‐Y hepaticojejunostomy stricture in an acute setting: A unique case and technique. Issue 1 (January 2014) - Pidigue, Rajan Seshiyer; Chinnusamy, Palanivelu; Jategaonkar, Priyadarshan Anand; Ramakrishnan, Parthasarathi; Subbiah, Rajapandian; Palanisamy, Senthilnathan; Natesan, Anand Vijai S; Palanivelu, Praveen Raj
Abstract Roux‐en‐Y hepaticojejunostomy stricture is a substantial problem that develops in 10%–30% of patients and requires frequent intervention. Although endoscopic/percutaneous approaches are preferred, especially for refractory stricture, open surgical reconstruction remains the gold standard. However, such an operation may be highly challenging. The recently developed covered, self‐expanding metallic stent is a useful option for such difficult cases. We present a case of recurrent Roux‐en‐Y hepaticojejunostomy stricture complicated by densely packed intrahepatic stones and suppurative cholangitis with failed percutaneous biliary draining. Enteroscopic manipulations were unfeasible, and the case was successfully managed by the laparoendoscopic approach. If treating surgeons have the necessary expertise, this technique may be considered in such difficult scenarios.